Pengaruh Return on Asset, Return on Equity, Net Profit Margin Terhadap Harga Saham pada Industri Makanan dan Minuman di Bursa Efek Indonesia Periode 2018-2020 - Allan B Pasaribu; Harlyn Siagian (Universitas Batanghari Jambi, 2022)
The study was made by the author to find out the effect of ROA, ROE, and NPM simultaneously on stock prices and in testing the effect of ROA, ROE, and NPM partially on stock prices, the sample was 13 companies from 30 food and beverage sub-sector companies listed in the Indonesian Stock Exchange. IDX in 2018 - 2020, so that the total sample of 33 variables used is stock price the dependent variable while ROA, ROE and NPM are independent variables. In analyzing using multiple linear regression analysis. The sampling in this study was carried out using purposive sampling. The results of this research show that simultaneously ROA, ROE, and NPM variables have a significant effect on stock prices. While partially ROA, ROE has a positive effect while NPM has a negative but not significant effect on stock prices.